Nonsteroidal anti-inflammatory drugs in the epoch of biological therapy - A E Karateev; A E Karateyev (Современная ревматология, 2008)
The risk and benefit of using nonsteroidal anti-inflammatory drugs (NSAIDs) are considered. The adverse reactions of NSAIDs are noted to be a serious problem, but they are predictable and preventable. Consideration of risk factors, adequate and timely treatment of comorbidity, and implementation of appropriate prophylactic measures minimize the likelihood of menacing complications. It is concluded that the benefit of the administration of NSAIDs generally overweighs the possible risk of their undesirable adverse effects.